Perlindungan Anak Di Media Sosial Dalam Perspektif Islam - Aflahussabilah; Naila Rizki Syafitri Lubis; Neiza Amanda Salam; Mutiara Syafitri Hasibuan; Sari Ati Amelia (Albayan Journal of Islam and Muslim Societies, 2025)
The concept of power in Fiqh Dusturiyah constitutes an important aspect of Islamic political thought that regulates the relationship between authority, governance, and public welfare. In the contemporary context, the study of power in Fiqh Dusturiyah has become increasingly relevant to the development of constitutional governance and democratic systems. This research aims to analyze the concept of power in Fiqh Dusturiyah and examine its relevance to the Indonesian constitutional system. The study employs normative legal research using conceptual and library research approaches. Data were collected from classical Islamic political literature, constitutional law references, scholarly journals, and other relevant academic sources. The findings reveal that power in Fiqh Dusturiyah is viewed as an amanah (trust) that must be exercised based on the principles of justice (al-'adalah), consultation (shūrā), and public welfare (maṣlaḥah). Furthermore, Fiqh Dusturiyah recognizes the division of governmental authority into legislative (al-sulṭah al-tashrī‘iyyah), executive (al-sulṭah al-tanfīdhiyyah), and judicial (al-sulṭah al-qaḍā’iyyah) functions, which aim to prevent the concentration of power and ensure governmental accountability. The study also demonstrates that these principles are substantially relevant to the Indonesian constitutional system, particularly in relation to the rule of law, democracy, popular sovereignty, and the implementation of checks and balances. This research concludes that the values embedded in Fiqh Dusturiyah can serve as an ethical foundation for strengthening democratic, accountable, and justice-oriented governance within the framework of the Indonesian constitutional system.